The Influence of Social Media Influencer on Students’ Interest in Investing in the Capital Market - Andi Tenri Ulmi; Cepi Pahlevi; Muhammad Sobarsyah (Magister Management, Hasanuddin University, 2022)
The purpose of this study is to find out how social media influencers attract students' interest in investing. With the use of 150 students as samples for this research, the study targeted students at state universities in Makassar. Before conducting the main analysis, limited numbers of data are first evaluated to ensure their validity and reliability. The collected data are then processed with classical-assumption tests before examining simple regression analysis. On the basis of statistical analysis, the results of the study showed that social media influencers have significantly affected students' interest in investing in the capital market. This finding strengthens the existing literature that repeated information received could influence decisions. Gallery at university is seemingly an effective way to target students to highly participate and form student attractive in investing in the capital market.